Exploring the Links Between Music and Changing Conceptions of Consciousness: Some Implications for Education - Terry Hyland (International Journal of Educational Excellence and Innovation, 2024)
Music, in all its forms, has long played an integral role in human life, functioning not merely as a form of cultural activity and entertainment but also as a profound conduit for exploring the links between the artistic endeavour and forms of human consciousness.  As such, music is, quite rightly, entitled to a central place in educational activity yet – as with other aspects of the humanities, literature and the fine arts – it is not always emphasized sufficiently in the curricula of educational systems which tend to be dominated by job-related academic outcomes and test-driven summative assessment models. This article seeks to re-assert the importance of music as a crucial curriculum subject by exploring its myriad nature, forms and purposes, particularly its positive role in terms of the cognitive/affective personal development of learners and the ways in which it can contribute to collective social ethics and cultural enrichment. As part of this exploration, the nature of music will be examined against the background of changing philosophical perspectives on consciousness, in particular, the growing critiques of the failure of scientific materialism to solve the “hard problem” of consciousness offered by new idealist thinkers who posit the notion that consciousness is the ultimate ontological primitive.  It will be suggested that the richness of this discourse – in linking the new idealist models to the artistic endeavour – can serve to reinforce the valuable contribution music can make to educational development at all levels.